Possible occurrence of a genetic bottleneck in dengue serotype 2 viruses between the 1980 and 1987 epidemic seasons in Bangkok Thailand - Sittisombut, Nopporn; Sistayanarain, Anchalee; Cardosa, Mary Jane; Salminen, Mika; Damrongdachakul, Supaporn; Kalayanarooj, Siripen; Rojanasuphot, Suntharee; Supawadee, Jiraporn; Maneekarn, Niwat (The American Society of Tropical Medicine and Hygiene, 1997)
Cocirculation of two genetic subtypes of denguc serotype 2 viruses was first observed in the 1980 epidemic season in Thailand. To further delineate the evolutionary history and the contribution of these subtypes to subsequent epidemics, we determined the envelope glycoprotcin gene sequence of 20 dengue serotype 2 viruses isolated from infected patients during 1987 and compared them with those derived from earlier years. Subtype ifia strains represented the majority (18 of 19) of dengue type 2 viruses derived from Bangkok metropolitan area, whereas all three strains from a province in the northeastern region belonged to subtype Ilib, indicating uneven local distni bution of dengue subtypes within the same year. Three types of sequence variation were identified in both subtypes: substitutions that were unique to individual strains; substitutions that were shared among all subtype HIa on Ilib viruses of both the 1980 and 1987 epidemics; and those that were shared only among all subtypes lila or IIlb viruses of the 1987 epidemic, but were absent from the corresponding subtypes of 1980. While the first and second types of substitution were indicative of the most recent random mutations and previous mutations that had been fixed in virus populations, respectively, the third type suggested possible occurrence of a genetic bottleneck and subsequent expan sion of one or a limited number of subtype lila strains in Bangkok between 1980 and 1987. Immunobbot analysis of intracellular NS1 antigen with anti-NS1 monocbonal antibodies also revealed antigenic heterogeneity of the NSl protein that correlated with the subdivision based on envelope protein variation.